Autonomic response to tactical pistol performance measured by heart rate variability - Thompson, A. G.; Swain, D. P.; Branch, J. D.; Spina, R. J.; Grieco, C. R. (The Journal of Strength and Conditioning Research, 2015)
This study evaluated changes in autonomic tone during a tactical pistol competition. At rest and during a match, heart rate variability (HRV) was examined in 28 healthy subjects. Heart rate variability time-domain variables (including interbeat interval [IBI]) and frequency-domain variables (low frequency [LF], high frequency [HF], total power [TP]) measured during shooting were subtracted from those measured during rest to produce ?s. The shooting task involved several, rapid tactical maneuvers. Raw time to completion and inaccurate shots (points down [PDs]) were recorded and combined to form a match score where lower values indicated superior shooting performance. Mean (±SD) raw time was 135.9 ± 34.1 seconds, PDs were 78 ± 34, and match score was 175.3 ± 39.8. Shooting decreased IBI (i.e., increased heart rate) and LF. dLF, dHF, and dTP were independent of dIBI. Raw time was significantly (p = 0.05) correlated to shooting IBI (r = 0.404) and dIBI (r = -0.426). Points down were significantly correlated to dTP (r = 0.416) and dLF (r = 0.376). Match score was significantly correlated to dIBI (r = -0.458), dHF (r = 0.467), dLF (r = 0.377), and dTP (r = 0.451). In conclusion, individuals with a greater decrease in IBI (and thus heart rate) performed better by accomplishing the match faster. Individuals with less change in stress-related HRV measures (LF, HF, and TP) performed better through improved accuracy. Thus, HRV-derived sympathetic response is significantly related to shooting performance and should be used to assess marksmanship effectiveness under duress.